If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6.9m + 1.96 = -49.79 Reorder the terms: 1.96 + 6.9m = -49.79 Solving 1.96 + 6.9m = -49.79 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1.96' to each side of the equation. 1.96 + -1.96 + 6.9m = -49.79 + -1.96 Combine like terms: 1.96 + -1.96 = 0.00 0.00 + 6.9m = -49.79 + -1.96 6.9m = -49.79 + -1.96 Combine like terms: -49.79 + -1.96 = -51.75 6.9m = -51.75 Divide each side by '6.9'. m = -7.5 Simplifying m = -7.5
| 0.2x+0.4=3.6 | | 7.7x=-60.06 | | x-4=7.26 | | 10-6x-4+8x=12 | | 0=35-5x-2x | | -5y=4.95 | | p(4b-1)=2(9b+3) | | x+3.1=7.3 | | 14s^2-167st-12t^2=0 | | x^2+5x+31= | | 0=7m+4-3m | | x+10=-30 | | (x+5)(3x-9)=0 | | s=2*3.14*r^2+2*3.14*r*h | | 2(2t-3)=6(t-2) | | 57x+4334635x-30409234809x=28934237409x+23423423x*12312321x | | 7t-8=2+5t | | -2+p+2p+2=-12 | | 5m-12=-10+4m | | -36-b-4b=64 | | 5m+1=-23 | | 11.3-7.2=-3.82 | | 1.3-7.2=-3.82 | | 8.4s-s=14.8 | | -5z+3z-7=8z-1-6 | | 3x-2=4x-8 | | 7n^2-43n+6=0 | | n^2=n | | 7p^2-27p-40=0 | | 5a=20 | | -7=2y-3-3y | | 3x-7(-2x+8)=-5 |